Bibliometric Analysis of Financial Technology Adoption by MSMEs in Indonesia - Nurkholik, Adam; Sitorus, Anggi Pratiwi; Oktavia, Shintami; Simanjuntak, Loranty Folia; Azhari, Shofwan Sasri; Sormin, Imanuddin Husayn; Gavriel, Lemuel Hezekiah; Evani, Ruthania; Tangkas, Maria Gabriel Oktriana (Jurnal EMT KITA, 2026)
This research aims to map the knowledge architecture and research landscape regarding the adoption of financial technology by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Although MSMEs are vital to the national economy, contributing 61% of the GDP, a comprehensive understanding of research trends, collaboration networks, and thematic gaps remains fragmented. To bridge this gap, this study presents a helicopter view thru a comprehensive literature synthesis. This research uses a bibliometric analysis design. Data was collected from the leading database Dimension.ai using specific keywords. Then, the data was analyzed to visualize citation networks, co-authorship, and keyword mapping using VOSviewer software. The results revealed that the research focus was divided into three main thematic clusters: Cluster Red (Islamic fintech, P2P lending), Cluster Green (digital economy, technology adoption), and Cluster Blue (MSME performance and risk management). The collaboration network shows a strong pattern, dominated by key authors affiliated with major universities in Indonesia, such as Airlangga University and the University of Indonesia. Nevertheless, reputable international journals (Heliyon, Sustainability) remain the primary citation references, highlighting a gap between national research productivity and global citation rates. This research theoretically confirms the shift in fintech adoption research by incorporating contextual and structural dimensions.